STUDENTS’ PERCEPTION TOWARD LECTURER OF ENGLISH IN TEACHING PERFORMANCE (A CASE STUDY AT INSTITUTE OF HEALTH SCIENCE SITI KHADIJAH PALEMBANG) - Nyayu Yayu Suryani (Universitas PGRI Palembang, 2015)
ABSTRACTThe main problem of this research “What are the teaching performance of the teacher/lecturer of English based on students’ perception related to the questionnaire given?”. Therefore, the main purpose of this study is to find out the students’ perception about the teacher of English in teaching performance at Institute of Health Science Siti Khadijah Palembang related to the questionnaire given. The population of this research was the first semester students of Institute of health Science Siti Khadijah Palembang . They were 40 students taken as sample. A descriptive method was used in this research. the data were obtained by means of questionnaire. Based on the result of the data analysis, the students’ perception toward their teacher’s performance in teaching covered seven aspect were as follows: (a) Preparation of Teaching, (b)Subject matter, (c)Submission of Teaching Materials, (d) Lecturer Competence, (e) Class Management and Academic Atmosphere, (f) Evaluation of Lesson and (g) Subject Matter Relevance.it concluded that most of the students’ perception about the teacher of English in teaching performance at Institute of Health Science Siti Khadijah Palembang give good perception.Key words : Students’ Perception, The Teacher/lecturer of English, Teaching Performance